2021
DOI: 10.3389/fimmu.2021.645478
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of NK Cell Cytotoxic Function With Elotuzumab and Daratumumab Promotes Elimination of Circulating Plasma Cells in Patients With SLE

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by multiple cellular and molecular dysfunctions of the innate and adaptive immunity. Cytotoxic function of NK cells is compromised in patients with SLE. Herein, we characterized the phenotypic alterations of SLE NK cells in a comprehensive manner to further delineate the mechanisms underlying the cytotoxic dysfunction of SLE NK cells and identify novel potential therapeutic targets. Therefore, we examined PBMC from SLE patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…NK cells in SLE exhibit an impairment with cytotoxic function. Increasing studies have suggested that restoration of NK cell cytotoxic function by regulating SLAMF7 and CD38 can promote plasma cell deletion and contribute to SLE improvement [35]. Our data has implicated a declined level of NK cells in SLE patients, which is consistent with ndings in a previous study [32].…”
Section: B Cells Play a Critical Role In Sle Pathogenesissupporting
confidence: 92%
“…NK cells in SLE exhibit an impairment with cytotoxic function. Increasing studies have suggested that restoration of NK cell cytotoxic function by regulating SLAMF7 and CD38 can promote plasma cell deletion and contribute to SLE improvement [35]. Our data has implicated a declined level of NK cells in SLE patients, which is consistent with ndings in a previous study [32].…”
Section: B Cells Play a Critical Role In Sle Pathogenesissupporting
confidence: 92%
“…Disease activity was assessed using the Safety of Estrogens in Lupus Erythematosus National Assessment modification (SELENA)-SLEDAI and the Physician's Global Assessment score (PGA) 33 . We categorized SLE patients into three groups of disease activity: inactive (SELENA-SLEDAI 0–3), moderate (SELENA-SLEDAI 4–10) and active (SELENA-SLEDAI > 10) 58 . Clinical SELENA-SLEDAI was used to evaluate disease activity, while excluding complement and anti-dsDNA from the score.…”
Section: Methodsmentioning
confidence: 99%
“…Cryopreserved PBMC from SLE and matched HC were processed and analyzed as previously published 58 . Lists of mass cytometry antibodies are provided in the Supplementary Table 2 and were previously described 58 .…”
Section: Methodsmentioning
confidence: 99%
“…Cryopreserved PBMC from SLE and matched HC were processed and analyzed as previously published (5). Lists of mass cytometry antibodies are provided in the Supplementary Table 3 and were previously described (5). To avoid batch effect, PBMCs of SLE and matched HC were barcoded, processed, and examined at the same time.…”
Section: Mass Cytometrymentioning
confidence: 99%
“…Cryopreserved PBMC from SLE and matched HC were processed and analyzed as previously published (5). Lists of mass cytometry antibodies are provided in the Supplementary Table 3 and were previously described (5).…”
Section: Mass Cytometrymentioning
confidence: 99%